2017
DOI: 10.4103/ijmy.ijmy_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and laboratorial profile of patients with isolation of nontuberculous mycobacteria

Abstract: In the study region, mycobacteriosis most affected adult males with low schooling. Most patients presented comorbidities in particular co-infection with the HIV virus. M. avium is the most prevalent species in the region with the M. abscessus/M. massiliense/M. bolletii species being the main cause of nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A limitation of the present study is the small number of NTM cases; however, it provided essential data on the clinical and epidemiological profile and treatment of NTM. The current research from Mato Grosso significantly contributes to data on the prevalence and distribution of NTM species isolated in Brazil (Ueki et al, 2005;Pedro et al, 2017;Carneiro et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of the present study is the small number of NTM cases; however, it provided essential data on the clinical and epidemiological profile and treatment of NTM. The current research from Mato Grosso significantly contributes to data on the prevalence and distribution of NTM species isolated in Brazil (Ueki et al, 2005;Pedro et al, 2017;Carneiro et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…(3) The limitation of M. simiae studies, particularly in the Middle East region, including Iran (11,12,27,34).…”
Section: Discussionmentioning
confidence: 99%
“…(24) Recent studies conducted in Brazil have reported that M. avium is the NTM species most often isolated from respiratory specimens in HIV-infected patients. (25,26) The present study was carried out at a referral hospital for HIV-infected patients, located in the Brazilian state of Rio Grande do Sul, where the prevalence of HIV infection is 38.3 cases/100,000 population, the second highest among all of the states in the country. (27) Among the patients infected with NTM, most were infected with M. avium (72.0%), and 55.5% of those patients were coinfected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Recent studies conducted in Brazil have reported that M. avium is the NTM species most often isolated from respiratory specimens in HIV-infected patients. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%